Capital asset pricing model and pricing of Islamic financial instruments - Hakim, Shabir Ahmad (King Abdulaziz University, 2016)
The prohibitions of ribā (interest) and trading in non-ḥalāl businesses in Islam redefines investment universe assumed by Capital Asset Pricing Model (CAPM). In Islamic investment world, risk-free asset and market portfolio with non-ḥalāl constituents are irrelevant. We propose two-versions of Sharīʿah-compliant CAPM that use Sharīʿahcomplaint market portfolio and are free of risk-free asset. We test the proposed models together with conventional CAPM in Bursa Malaysia using three- and ten-year data. The test results of the models with three-year data reveal remarkable similarity between versions of Sharīʿah-compliant models. Besides, Sharīʿah-compliant CAPM is as capable of explaining returns on Sharīʿah-complaint stocks as conventional CAPM is of explaining returns on all stocks.